1988
DOI: 10.3758/bf03209067
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stimulus similarity on different types of behavioral contrast

Abstract: Pigeons were trained on multiple schedules with component stimuli of different degrees of similarity. In Experiment 1, a two-component schedule was used in which the two stimuli were either two line orientations or a line orientation versus a diffuse color. Reinforcement rate was varied in one component to determine the effects of stimulus similarity on different aspects of behavioral contrast. Contrast in terms of average response rates (molar contrast) was larger with less similar stimuli. Local contrast eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…However, a is a highly derived value that combines information about rates in both multiple-schedule components. Furthermore, as seen in Williams (1988), local effects based on a differ from those based on rates during the unchanged component. This point is important because White, Pipe, and Mclean (1984) found that a increased with increasing dissimilarity among signaling stimuli; moreover, this effect was most pronounced at component onset.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a is a highly derived value that combines information about rates in both multiple-schedule components. Furthermore, as seen in Williams (1988), local effects based on a differ from those based on rates during the unchanged component. This point is important because White, Pipe, and Mclean (1984) found that a increased with increasing dissimilarity among signaling stimuli; moreover, this effect was most pronounced at component onset.…”
Section: Discussionmentioning
confidence: 99%
“…Although these effects were not strong enough to yield within-eomponent ratios significantly different from 1.0, baseline was not an effective reference condition. Thus, as in Williams's (1988) study, local contrast in the present report is defined in terms of patterns obtained within experimental conditions. A second source of confusion occurs when within-eomponent and between-eomponent definitions are poorly distinguished.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations